Postgraduate Training Experiences Among International Registrars, at a Health Sciences Faculty, in South Africa - Baheir, Baheir (Department of Public Health and Family Medicine, 2024)
Background: The lived experiences of International Registrars (IRs) at a health sciences faculties in South Africa (SA) has not been documented, given the high numbers of IRs choosing SA as the destination of choice for medical specialization. This study addresses the question: what are the experiences of IRs pursuing medical specialization in SA?. The findings may help future IRs make informed decisions when choosing their study destination. It could also assist supervisors and program managers to anticipate some of the challenges that IRs face. Methods: A qualitative design using interpretive phenomenology approach was employed. using semistructured face-to-face interviews, data was collected directly from IRs, and checked for accuracy using a focus group discussion. Results: 2 major themes were developed: Negative experiences were subdivided into 4 subsections: registration and administrative barriers, structural and policy related-challenges, challenges related to teaching, supervision and clinical training, and finally challenges related to life outside university. The second theme documented positive experiences. Conclusion: We described several important issues affecting externally funded IRs arriving for postgraduate training at the study site. Some recommendations are made for practical implementation and future research.